Insomnia among medical students: a cross-sectional study - Shakeel, Hassan Abdullah; Maqsood, Hamza; Ishaq, Asher; Ali, Basit; Hussain, Humza; Khan, Ali Raza; Shah, Syed Asfand Yar (International Journal of Research in Medical Sciences, 2019)
Background: Insomnia, the most common sleep disorder, is the perception or complaint of inadequate or poor-quality sleep because of one or more of the following conditions: difficulty in falling asleep, frequent waking up during the night with difficulty for returning to sleep, waking up too early in the morning, or unrefreshing sleep. It is the most common sleep related complaint reported in the primary care setting. Medical students are specially at risk of developing insomnia and its consequences. This study evaluates the prevalence and severity of insomnia in medical students in relation to certain socio-demographic factors like age, sex and class of education. Methods: A questionnaire based study was done on 135 medical students of Nishtar Medical University, Multan chosen on basis of random sampling to test the prevalence of insomnia using Athens Insomnia Scale (AIS). Out of these students 75 were males and 60 were females. Students were interviewed to obtain information about age, sex and academic year of education. Results: According to Athens insomniac scale scoring, 55 (40.74%) students were found insomniac while 80 (59.25%) were non-insomniac. Out of 55 insomniac students, 23 (41.81%) were males while 32 (58.18%) were females. Likewise, out of 80 non-insomniac students, 52 (65%) were males while 28 (35%) were females. The prevalence of insomnia in medical students was found to be increased with the increasing age. It was found that the females have more insomnia prevalence as well as more severe signs and symptoms of insomnia. Moreover, final year students tend to show more prevalence and severity of insomnia than their juniors. Conclusions: According to this study, 2 out of every 5 students were insomniac. Demographic comparison showed that the prevalence and severity of insomnia was more in females and final year students. Also, it was increasing side by side with increasing age.